Compiling Multicopy Single-Stranded DNA Sequences from Bacterial Genome Sequences - Wonseok Yoo; Dongbin Lim; Sangsoo Kim (Genomics & Informatics, 2016)
A retron is a bacterial retroelement that encodes an RNA gene and a reverse transcriptase (RT). The former, once transcribed, works as a template primer for reverse transcription by the latter. The resulting DNA is covalently linked to the upstream part of the RNA; this chimera is called multicopy single-stranded DNA (msDNA), which is extrachromosomal DNA found in many bacterial species. Based on the conserved features in the eight known msDNA sequences, we developed a detection method and applied it to scan National Center for Biotechnology Information (NCBI) RefSeq bacterial genome sequences. Among 16,844 bacterial sequences possessing a retron-type RT domain, we identified 48 unique types of msDNA. Currently, the biological role of msDNA is not well understood. Our work will be a useful tool in studying the distribution, evolution, and physiological role of msDNA.